2013
DOI: 10.1038/emboj.2013.24
|View full text |Cite
|
Sign up to set email alerts
|

End-joining inhibition at telomeres requires the translocase and polySUMO-dependent ubiquitin ligase Uls1

Abstract: In eukaryotes, permanent inhibition of the nonhomologous end joining (NHEJ) repair pathway at telomeres ensures that chromosome ends do not fuse. In budding yeast, binding of Rap1 to telomere repeats establishes NHEJ inhibition. Here, we show that the Uls1 protein is required for the maintenance of NHEJ inhibition at telomeres. Uls1 protein is a non-essential Swi2/Snf2-related translocase and a Small Ubiquitin-related Modifier (SUMO)-Targeted Ubiquitin Ligase (STUbL) with unknown targets. Loss of Uls1 results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 53 publications
2
51
0
Order By: Relevance
“…Sumoylation of K240/246 of Rap1 was recently shown to be important for telomere homeostasis (Lescasse et al 2013). However, we found that preventing sumoylation of these two lysine residues, as well as various combinations of other N-terminal and C-terminal residues, had no effect on Rap1 sumoylation, RPG transcription, and cell viability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sumoylation of K240/246 of Rap1 was recently shown to be important for telomere homeostasis (Lescasse et al 2013). However, we found that preventing sumoylation of these two lysine residues, as well as various combinations of other N-terminal and C-terminal residues, had no effect on Rap1 sumoylation, RPG transcription, and cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…3A, bottom). Interestingly, several reports have indicated that Rap1 may be a Sumo target, although its relevance for transcription was never explored (Wohlschlegel et al 2004;Denison et al 2005;Hang et al 2011;Lickwar et al 2012;Albuquerque et al 2013;Lescasse et al 2013). Encouraged by these findings, we decided to focus on sumoylation of Rap1 at RPG promoters.…”
Section: Sumoylation At Rpgs Occurs At Rap1 Binding Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Uls1 interacts with SUMO and Ubc4, the E2 ubiquitin-conjugating enzyme, while uls1D cells accumulate high-molecular-weight SUMO conjugates, which led to its classification as a SUMO-targeted ubiquitin ligase (STUbL) (Uzunova et al 2007). Additionally, Uls1 was proposed to function in nonhomologous end joining inhibition by dislodging poly-SUMOylated Rap1 molecules from telomeres (Lescasse et al 2013). However, enzymatic activity of Uls1 has never been biochemically demonstrated and little is known about its targets.…”
mentioning
confidence: 99%
“…Importantly, roles of Uls1 in DNA metabolism require an ATP-dependent translocase activity, RING domain, and SIMs (Cal-Bąkowska et al 2011;Chi et al 2011;Lescasse et al 2013;Tan et al 2013;Kramarz et al 2014). It can therefore be hypothesized that Uls1 may regulate DNA-repair-pathway choice at the sites of replication-associated DNA damage by modifying SUMOylation status and thus the abundance and/or activities of its target proteins.…”
mentioning
confidence: 99%